Higher Education Institutions in the Knowledge Triangle - Mario Cervantes (Foresight and STI Governance, 2017)
This paper discusses some of the policy issues and best practices aimed at enhancing HEIs performance and improving their impact on society and the economy within the knowledge triangle. The knowledge triangle concept aims at exploring ways to better align and integrate the research, education and innovation functions of HEIs. The paper describes the contents of the knowledge triangle, HEI performance through the lens of this concept, policies to promote the knowledge triangle in HEIs, as well as potential contradictions in relation to other knowledge producers, such as public research centers and companies.